2021
DOI: 10.3389/fmicb.2021.713703
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Upper Respiratory Microbiota to Reduce Incidence and Severity of Upper Respiratory Viral Infections: A Literature Review

Abstract: There is a high incidence of upper respiratory viral infections in the human population, with infection severity being unique to each individual. Upper respiratory viruses have been associated previously with secondary bacterial infection, however, several cross-sectional studies analyzed in the literature indicate that an inverse relationship can also occur. Pathobiont abundance and/or bacterial dysbiosis can impair epithelial integrity and predispose an individual to viral infection. In this review we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 116 publications
(142 reference statements)
0
9
0
Order By: Relevance
“…Our findings suggest its high prevalence in both CF and NCFB. Cutibacterium (formerly Propionibacterium ) is also found in the upper respiratory tract [ 51 ], but in this study, it emerged as a major component of the lung microbiota of both disease cohorts. The NCFB cohort also exhibited three exclusive genera in its core: Capnocytophaga , Lautropia , and Treponema .…”
Section: Discussionmentioning
confidence: 78%
“…Our findings suggest its high prevalence in both CF and NCFB. Cutibacterium (formerly Propionibacterium ) is also found in the upper respiratory tract [ 51 ], but in this study, it emerged as a major component of the lung microbiota of both disease cohorts. The NCFB cohort also exhibited three exclusive genera in its core: Capnocytophaga , Lautropia , and Treponema .…”
Section: Discussionmentioning
confidence: 78%
“…In studies that do investigate respiratory microbiota interventions to prevent RTIs, several commensals have been identified that maintain a healthy URT microbiota and inhibit pathogenic growth. An overview of commensal respiratory bacteria with potential for probiotic use is presented in a recent review by Nesbitt et al [35].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, multiple microbe species that have been found to be more prevalent in non-CL/P subjects than in CL/P patients may have a positive effect on human health. For example, certain species of Dolosigranulum may be negatively correlated with the incidence of particular respiratory maladies and enhance the immune response of the respiratory epithelium ( Islam et al., 2021 ; Nesbitt et al., 2021 ) and appear to provide resistance to ear infections ( Pettigrew et al., 2012 ; Lappan et al., 2018 )—a common complaint of CL/P patients ( Flynn et al., 2009 ). Strikingly, lack of Mitsuokella multacida , another species specific to the non-CL/P condition, is associated with the early development of colon cancer ( Arafat, 2020 ; Elkholy et al., 2020 ), although its presence may be linked to squamous cell lung cancer as well ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%